Analisis Pemanfaatan Teknologi Informasi & Digital Bisnis Dalam Usaha Mikro Kecil dan Menengah (UMKM) di Wilayah Kerja BPSDMP Kominfo Bandung - -, Rina Fitriani; Aswin Dewanto Hadisumarto; HS. Sulistyowati; Shofiyyah Ahsanti (LPPM STMIK IKMI Cirebon, 2025)
Evaluating the benefits of social media, digital wallets, marketplaces, and the Government's efforts in providing digital training to MSMEs for product marketing can be conducted through observation, interviews, and documentation. The purpose of this research is to analyze the benefits of Information Technology and Digital Business for MSMEs in the working area of BPSDMP Kominfo Bandung. The qualitative descriptive research method interprets the results using Data Triangulation. The research design begins with a literature review, followed by the development of research instruments. Subsequently, interviews are conducted and analyzed to derive conclusions. The research results prove a positive impact on MSME performance in terms of marketing effectiveness, operational efficiency, and customer communication.